Effect of an exercise program on physical-kinetic intelligence and the skills of dribbling and shooting in basketball among female students - Majeed, Sahar Hur (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The current research aimed to study the effect of an exercise program on physical-kinetic intelligence and the skills of dribbling and shooting in basketball among female students. The research community was composed of 102 female students in the second stage of the Physical Education and Sports Sciences College for Girls of Baghdad University, in the academic year 2021-2022. A total of 40 female students were the sample of the study: 20 female students in the control group and 20 female students in the experimental group. After the implementation of the exercise program, there were significant improvements from pre-tests to post tests in the two groups (control and experimental groups), in physical-kinetic intelligence and in the skills of dribbling and shooting in basketball. When comparing the differences between the post tests of both groups, the results of the experimental group were significantly better than the results of the control group. In conclusion, the exercise program used in this study is effective to improve physical-kinetic intelligence and the skills of dribbling and shooting in basketball among female students.